Use of Facebook by Secondary School Students at Nuku'alofa as an Indicator of E-Readiness for E-Learning in the Kingdom of Tonga - Hans Tobias Sopu (Athabasca University Press, 2016)
The Kingdom of Tonga is an isolated least developing country located on the northeast of New Zealand with a population of 103,252 (2011 census) and with a gross domestic product per capita of USD $2,545.20.  Before educational systems in a least developing country like the Kingdom of Tonga begin employing e-learning, an assessment of the current situation of students and learning institutions may contribute to its success. Using an appropriate assessment tool is important for accurately measuring the degree of e-readiness. In this study, we administered a survey to 186 students randomly selected from five secondary schools in the Kingdom of Tonga to measure Facebook usage as an index of e-readiness for e-learning. We found that a large percentage (81%) of secondary students use Facebook, and most (74%) of these students have used Facebook for two or more years. All (100%) students use a computer to access Facebook, and most also access Facebook through mobile phones (62%) or tablets (46%). We also found correlations between duration of having a Facebook account and other indicators of e-readiness. Our findings suggest that secondary students in the Kingdom of Tonga have developed e-readiness for e-learning through their use of Facebook.